Weight Loss Outcomes With Telemedicine During COVID-19 - Tchang, Beverly G.; Morrison, Chenel; Kim, Joon Tae; Ahmed, Farheen; Chan, Karina M.; Alonso, Laura C.; Aronne, Louis J.; Shukla, Alpana P. (Frontiers in Endocrinology, 2022)
Background: Amidst the COVID-19 pandemic, telemedicine was rapidly implemented to maintain patient care during quarantine. However, there is little data on how this transition may have impacted weight loss outcomes and interventions among patients with medically managed overweight or obesity. Methods: This was a retrospective observational study of adults who established care for medically managed obesity at the Weill Cornell Comprehensive Weight Control Center during September-November 2019 and May-July 2020 and who completed 6 months of follow-up. Weight loss outcomes and weight management interventions were explored and stratified by patient-provider interaction: in-person visits only, in-person and video visits, and video visits only. Results: Of 499 charts eligible for review, 245 (49%) returned for their 6-month follow-up visit and were included for analysis. Of 245 patients, 69 had in-person visits only (“in-person”), 85 started in-person and later switched to video visits (“hybrid”), and 91 had video visits only (“video”). All cohorts were predominantly white and female. Median ages were 56, 49, and 49 years; baseline median weights were 98.9, 96.8, and 93.0 kg; and baseline median BMIs were 35.3, 34.4, and 34.0 kg/m2 for in-person, hybrid, and video cohorts, respectively. The median percent weight changes over 6 months were not significantly different among cohorts: -4.3% [-8.5, -1.5] in the in-person cohort, -5.6% [-8.7, -2.2] in the hybrid group, and -5.8% [-9.7, -2.4] in the video cohort. The percent of patients who achieved ≥5% weight loss were also similar: 46.4%, 55.3%, and 59.3%, respectively. The median number of visits in the video cohort was more than in the in-person or hybrid groups (5 vs. 4). Median number of anti-obesity medications (AOMs) prescribed was similar among groups. The most common AOMs were metformin (all cohorts) followed by semaglutide 1.0 mg (in-person and video) or topiramate (hybrid). Conclusion: Patients on anti-obesity medications who were followed for 6 months via video or video plus in-person visits (hybrid) experienced clinically significant weight loss. Median number of AOMs were similar among groups, and the most common AOMs were metformin, semaglutide 1.0 mg, and topiramate. More investigation is required to compare telemedicine models with in-person care.